ANALISIS PENGARUH STRUKTUR APBD TERHADAP KINERJA KEUANGAN DAERAH DAN PERTUMBUHAN EKONOMI DI KABUPATEN dan KOTA se-JAWA TIMUR - yasin, muhammad; riyadi, slamet; ingga, ibrahim (JEB17 : Jurnal Ekonomi dan Bisnis, 2017)
AbstractEconomic growth is a process of changing a country's economic conditions on a sustainable basis to a better state for a certain period. Economic growth can be interpreted also as a process of increasing the production capacity of an economy which is realized in the form of an increase in national income. Variable Free PAD (X1) Measured using: (1) Taxes, (2) Non taxes, Balancing Funds (X2) Measured using: (1) Tax Sharing, (2) General Allocation Funds,(3) Special Allocation Funds. Routine expenditure (X3) Measured using: (1) Direct, (2)Indirect. Development spending (X4) Measured using: (1) Development, (2) Growth. Independent variables Economic growth Measured using: (1) Ratio of growth, (2) GDP constant, (3) Non-constant GDP. Variable Moderator relationship between independent variables with dependent Local financial performance Measured using: (1) Ratio of efficiency, (2) Effectiveness ratio, (3) Ratio of independence, (4) Activity ratio. economic growth with this means that if the regional income it will cause an increase also on theachievement of economic growth. which is very flexible in terms of its utilization causes the region more flexibility in planning budget allocation for development activities in accordance with its economic agenda which among others in the form of development of basic facilities and infrastructure that play a role in supporting optimal economic growth.Keywords: PAD, Balancing Fund, Routine Expenditure, Development Expenditure, Financial Performance, Economic Growth